Mind the gap: the cloud security skills shortage. Issue 8 (August 2021) - Campfield, Mike
Abstract : You don't need to know much about security to know that security skills are in short supply. Demand for cyber security expertise is exploding as cyberthreats become increasingly advanced, persistent and adept at evading detection.